2014
DOI: 10.4300/jgme-d-13-00349.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of the QR Reader to Provide Real-Time Evaluation of Residents' Skills Following Surgical Procedures

Abstract: Background A portable electronic method of providing instructional feedback and recording an evaluation of resident competency immediately following surgical procedures has not previously been documented in obstetrics and gynecology. Objective This report presents a unique electronic format that documents resident competency and encourages verbal communication between faculty and residents immediately following operative proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The key benefits of using QR codes for healthcare education lie in the ability to provide timely, multimodal information in a cost-effective manner. Several studies demonstrated an improvement in engagement from students or faculty [19,20,22,23,26,[39][40][41][42], which may be due to ease of use, availability and immediacy compared to other available methods of accessing information. Additional benefits lie in adaptability, simplicity of creation and potential environmental benefits of QR codes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key benefits of using QR codes for healthcare education lie in the ability to provide timely, multimodal information in a cost-effective manner. Several studies demonstrated an improvement in engagement from students or faculty [19,20,22,23,26,[39][40][41][42], which may be due to ease of use, availability and immediacy compared to other available methods of accessing information. Additional benefits lie in adaptability, simplicity of creation and potential environmental benefits of QR codes.…”
Section: Discussionmentioning
confidence: 99%
“…Four articles explore how QR codes can be used to improve trainee experience, either through improvement in feedback methods [39][40][41] or by recording procedures undertaken in a log book [42].…”
Section: Theme 4: Training Supportmentioning
confidence: 99%
“…5,[16][17][18][19][20][21][22][23] Real-time feedback via web-based platforms and mobile applications has been reported to facilitate feedback by properly and efficiently relaying constructive criticism to residents, 17,20 maintaining longitudinal records of resident progress based on milestones, 20 improving clinical practices such as handoffs or sign-outs, 20 tracking procedural skills checklists, and tracking other quality metrics. 17,[20][21][22][23] The results of this study showed myTIPreport achieved some of these goals by facilitating and storing workplace feedback on milestones and procedural skills. A systematic review reported that few published studies have examined feedback receptivity and feedback provision.…”
Section: Discussionmentioning
confidence: 99%
“…Four articles explore how QR codes can be used to improve trainee experience, either through improvement in feedback methods (32)(33)(34) or by recording procedures undertaken in a log book (35).…”
Section: Theme 4: Training Supportmentioning
confidence: 99%
“…Sobhani et al (32) and Reynolds et al (34) both investigated how feedback could be received through assigning an individual QR code to each student or resident that could then be scanned by a faculty member. In both cases, it was demonstrated that faculty found the QR-linked feedback form superior to the paper alternative.…”
Section: Theme 4: Training Supportmentioning
confidence: 99%